The effect of preoperative training provided to patients undergoing coronary artery bypass graft surgery on postoperative comfort: The effect of preoperative training on postoperative comfort - Şahin, Ayşe; Dığın , Figen (Journal of Surgery and Medicine, 2024)
Background/Aim: The most popular surgical procedure for treating coronary artery diseases is coronary artery bypass graft surgery. However, the comfort that patients experience after coronary artery bypass graft surgery varies considerably. The purpose of this study is to ascertain the impact of preoperative training on postoperative comfort in patients undergoing coronary artery bypass graft surgery. Methods: This study was conducted as a quasi-experimental research investigation the cardiovascular surgery clinic of Edirne Sultan Murat I State Hospital from December 2019 through December 2020. It included 46 patients aged 18–65 who were undergoing their first coronary artery bypass graft surgery and volunteered to participate. The patients in the experimental group (23 individuals), were provided preoperative training; no interventions were made with the patients in the control group. The General Comfort Questionnaire was administered to all of the patients prior to discharge. The necessary ethical and institutional approvals were obtained before the study. Transparent Reporting of Evaluations with Non-randomized Designs was used as the research reporting guideline. Results: The postoperative General Comfort Questionnaire total score (P<0.001), mean scores of all sub-dimensions (P<0.001) and comfort levels of the experimental group were higher than those of the control group (P<0.001). Preoperative training therefore had a positive impact on postoperative comfort level. Conclusion: Preoperative training provided to patients improved their postoperative comfort. It is recommended that surgical nurses increase patient comfort by providing patient training before coronary artery bypass graft surgery and that nurses should be supported in administering patient training.